Supervising graduate research - Jawan, Jayum (Universiti Putra Malaysia Press, 2013)
Supervising Graduate Research makes a good companion to both potential supervisors and research students. Many issues and challenges of supervising graduate research are discussed in this volume. Potential supervisors and research students can also get a feel of what they can expect from each other in the process of working on a research project together. Some of the main themes addressed in this volume are as follow: the issues and challenges of supervision; the process of building and maintaining good working relations between supervisors and their supervisees; the need to understanding the research environment and related support system; and the need to write and publish for both supervisors and research students as a mean by which they may lay claim to ownership of new findings or novel ideas. Discussion of these issues and challenges have benefitted greatly from the many real case examples and the many years of accumulated experiences that the team of academic.